Teenage sexuality: implications for controlling AIDS. Issue 9 (September 1989) - Curtis, H; Lawrence, C; Tripp, J
Abstract : A study on 761 teenagers aged 15-17 years showed that 56% of both sexes had had a steady or serious relationship. For about 40% of both sexes intercourse was a part of this relationship. Teenagers know how AIDS is transmitted, but only one third indicated personal concern about the epidemic. Only a fifth anticipate a single monogamous relationship. Significantly more girls than boys are planning to have fewer partners. Of these not anticipating monogamy three quarters mentioned the use of condoms. If education is to be effective in reducing the AIDS epidemic it must be sufficiently relevant to create and maintain changes in life style and must also educate teenagers before they have established patterns of behaviour.